EVALUACION COMPUTACIONAL DE LOS ENLACES DE LA ESTRUCTURA CRISTALINA DEL TOPACIO PRE-IRRADIACION CON NEUTRONES DEL REACTOR RP-10 - Gómez, Javier (2006)
It was evaluated by means of the method of calculate TB-LMTO-ASA the loading density, TWO and the structure of bands of the different components from the Topaz, with the objective to study enlaces of its crystalline structure, that to the being radiated later with neutrons in the nucleus of reactor RP-10 is the causes of the damage by the irradiation.